Potential dual inhibitors of PCSK-9 and HMG-R from natural sources in cardiovascular risk management - Mohd Waiz; Sahir Sultan Alvi; M. Salman Khan (EXCLI Journal : Experimental and Clinical Sciences, 2022)
Atherosclerotic cardiovascular disease (ASCVD) stands amongst the leading causes of mortality worldwide and has attracted the attention of world’s leading pharmaceutical companies in order to tackle such mortalities. The low-density lipoprotein-cholesterol (LDL-C) is considered the most prominent biomarker for the assessment of ASCVD risk. Distinct inhibitors of 3-hydroxy-3-methyl-glutaryl-CoA reductase (HMG-R), the chief hepatic cholesterogenic enzyme, are being used since last seven decades to manage hypercholesterolemia. On the other hand, discovery and the association of proprotein convertase subtilisin/kexin type-9 (PCSK-9) with increased ASCVD risk have established PCSK-9 as a novel therapeutic target in cardiovascular medicine. PCSK-9 is well reckoned to facilitate the LDL-receptor (LDL-R) degradation and compromised LDL-C clearance leading to the arterial atherosclerotic plaque formation. The currently available HMG-R inhibitors (statins) and PCSK-9 inhibitors (siRNA, anti-sense oligonucleotides, and monoclonal antibodies) have shown great promises in achieving LDL-C lowering goals, however, their life long prescriptions have raised significant concerns. These deficits associated with the synthetic HMG-R and PCSK-9 inhibitors called for the discovery of alternative therapeutic candidates with potential dual HMG-R and PCSK-9 inhibitory activities from natural origins. Therefore, this report firstly describes the mechanistic insights into the cholesterol homeostasis through HMG-R, PCSK-9, and LDL-R functionality and then compiles the pharmacological effects of natural secondary metabolites with special emphasis on their dual HMG-R and PCSK-9 inhibitory action. In conclusion, various natural products exhibit atheroprotective effects via targeting HMG-R and PCSK-9 activities and lipoprotein metabolism, however, further clinical assessments are still warranted prior their approval for ASCVD risk management in hypercholesterolemic patients.